CONSERVATION OF LONG-LIVED MARINE SPECIES: SOME HINTS FOR ADOPTING A POPULATION APPROACH: Conservação de espécies marinhas de vida longa: algumas dicas para adotar uma abordagem de populações - Santangelo, Giovanni (Arquivos de Ciências do Mar, 2022)
Long-lived species, whose life-span can amply exceed one century, play a fundamental role within marine communities. However, due to the short time windows covered by most research our knowledge of their demography is quite limited, consequently severely limiting the possibility of understanding their complex dynamics over the long run. Moreover, several aspects of the life-history of long-lived populations are largely unknown. This short review describes some examples of demographic analyses in terrestrial ecology, which are then applied to long-lived marine species. The ultimate aim is to suggest that wider application of demographic concepts and models could improve our ability to understand how these populations might respond to unusual increases in mortality rates due to Global Climate Changes and other sources of anthropogenic disturbance. In this framework, close, continuous, reciprocal and dialectic interaction between population mathematicians and field marine ecologists could greatly help to both design the necessary research and set out improved population dynamic models for such species. Such models would constitute an important first step in increasing our knowledge, and thereby implementing management plans for fostering the conservation of long-lived marine species, which too frequently have been defined by international conservation authorities. Keywords: demography, mortality tables, life-tables, gorgonian corals, cetaceans.